New species of Chrysosoma Guerin-Meneville (Diptera: Dolichopodidae), with a key to Chinese species - Zhu, Yajun; Yang, Ding (Zootaxa, 2005)
There are 21 species of the genus Chrysosoma Guérin-Méneville known from China. The following four species are added to the fauna of China: Chrysosoma nanlingense sp. nov., C. ruyuanense sp. nov., C. shixingense sp. nov. and C. zengchengense sp. nov. A key to the species of Chrysosoma from China is given. The distribution of the genus in China is also discussed.